My life is murder. Series 5 [videorecording (DVD)] - Harrop, Kim; Lawless, Lucy, 1968-; Redman, Amanda, 1957-; Jobe, Rawiri (Acorn TV, 2026)
From shady aquariums and elite cheer squads to creepy dolls and deadly island getaways, sharp-witted investigator Alexa Crowe (Lucy Lawless) tackles her most perplexing and personal case yet as old foes resurface and new secrets threaten those she loves.